Profil Kompetensi Literasi Sains Siswa SMA Konteks Fenomena Bencana Banjir Kabupaten Lamongan - Sunni, Fajriatul Mufarriha; Sunarti, Titin (Universitas Negeri Surabaya, 2023)
This research is the part of the development of Google Form assessment to measure physics scientific literacy skills in Kabupaten Lamongan Flooding Phenomena. The purpose of this research is to describe the competency profile of high school scientific literacy in the context of the flood phenomena in Kabupaten Lamongan. The research method used is descriptive quantitative by measuring students' scientific literacy skills using a physics assessment instrument with the topic of flooding phenomena in Kabupaten Lamongan on static and dynamic fluid which is distributed and worked by using the Gaoogle Form and has gone through the question quality test stage which states the question is a matter valid and appropriate. The population in the study consisted of 60 students of class XI MIPA 8 and XI MIPA 9 from a high school in Kabupaten Lamongan. The data analysis technique is quantitative descriptive analysis from the results of testing students' scientific literacy levels and response questionnaire analysis to find out student feedback to the test. The results of this study are that the majority of students at SMAN 1 Lamongan have scientific literacy skills in the medium category because students have been trained in some scientific literacy skills while learning, the competence to explain phenomena scientifically has an average of 52.22% in the medium category, the competence to evaluate and design scientific inquiry has an average of 61.87% in the high category, the competency of interpreting data and evidence scientifically is in the medium category with an average percentage of 58.46% the majority of students state that the scientific literacy instruments developed are more interesting than the calculation questions that are usually done at school, and using Google Forms in assessments can make it easier for students to understand and work on scientific literacy assessment questions. Keywords: Student profile, Kabupaten Lamongan Flooding Phenomena, Static and Dynamic Fluid